1988
DOI: 10.1111/j.1755-3768.1988.tb04051.x
|View full text |Cite
|
Sign up to set email alerts
|

The human choriocapillaris in organ culture

Abstract: 4 x 4 mm pieces of human eye walls consisting of the sclera, the choroid and the pigment epithelium were kept in organ culture for 1 month and studied with light and transmission electron microscopy comparing the findings with normal tissue. After 1 month the choriocapillaris still had open vessel lumina lined with flattened endothelial cells containing organelles and vesicles on both inner and outer cell membranes. The endothelial cells lost their fenestrations and polarity in regard to the location of cell n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In previous studies, tissue cultures (Tso et al 1973;Overskott Vatne & Nicolaissen 1988;Fiskaadal et al 1992), choroidal cells from animals (Chader et al 1982; Morse et al 1989;Morse & Sidikaro 1990) or isolated subpopulations from the human choroid (Hu et al 1993) have been used to study the physiology of the choroid. Few attempts have been made to study the outgrowth of human choroidal cells in vitro ), characterize these cells and to investigate factors influencing their growth and behaviour.…”
mentioning
confidence: 99%
“…In previous studies, tissue cultures (Tso et al 1973;Overskott Vatne & Nicolaissen 1988;Fiskaadal et al 1992), choroidal cells from animals (Chader et al 1982; Morse et al 1989;Morse & Sidikaro 1990) or isolated subpopulations from the human choroid (Hu et al 1993) have been used to study the physiology of the choroid. Few attempts have been made to study the outgrowth of human choroidal cells in vitro ), characterize these cells and to investigate factors influencing their growth and behaviour.…”
mentioning
confidence: 99%
“…It has previously been shown that human choriocapillaris and choroidal cells seeded on Bruch's membrane can be studied in controlled tissue culture conditions (Overskott Vatne 1988;Nicolaissen et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Incubation was for 24 hours at 37 o C in 5% CO 2 . The choriocapillaris has been shown to survive for up to one month in organ culture, so 24 hours was well within the anticipated survival curve for the tissue(135).To quantify the ICAM-1 protein expression of tissues from the C5a and control organ cultures, quantitative PCR was used. RNA was isolated from four C5a treated and four control organ culture punches from one human donor using the RNeasy mini kit according to manufacturer's instructions (Qiagen, Valencia, CA).…”
mentioning
confidence: 99%